Drug Insurance and Psoriasis Severity: A Retrospective Cohort Study - Laurence Mainville; Hélène Veillette; Paul R. Fortin (Journal of Health Economics and Outcomes Research)
**Background:** Prescription drug insurance in Canada is constituted of a patchwork of public and private insurance plans. The type of drug insurance may have a negative impact on access to treatment for patients covered by public plans compared with private plans. **Objectives:** In patients with psoriasis treated with advanced therapy in public vs private drug insurance groups, we compared: (1) psoriasis severity scores when an advanced therapy was prescribed, (2) psoriasis severity scores at follow-up, (3) treatment response, and (4) delay between prescription and first dose of advanced therapy. **Methods:** This unicentric, retrospective cohort study included patients suffering from psoriasis treated by advanced therapy, dermatologist-prescribed between September 2015 and August 2019, in a tertiary academic care center in Québec City, Canada. Data were collected from medical records. **Results:** Patients treated with an advanced therapy for psoriasis covered under the provincial public drug insurance plan (n = 78) and under a private drug plan (n = 93) did not differ regarding the studied outcomes. Patients’ characteristics differed between groups. Patients in the public group were older (_P_ < .0001), more socioeconomically deprived (_P_ < .05), and more likely to benefit from compassion from the industry to access a prescribed medication free of charge (_P_ < .0001) compared with patients from the privately insured group. **Discussion:** The high prevalence of compassionate programs from the industry in the public insurance group (42% vs 14%), and the high prevalence of psoriasis on difficult-to-treat areas (face, genitalia, and/or palmoplantar areas) in our cohort (85.4%) may mask differences in access to advanced therapy between the two groups. **Conclusions:** Prescribers of advanced therapy can be reassured, as we found no inequality in access or care based on patients’ drug insurance coverage.